Steering Differential Control of Two-wheeled Direct-drive Electric Vehicle Based on Master-slave Strategy - 孙宜标; 王哲; 丁惜瀛 (Kongzhi Yu Xinxi Jishu)
Two-wheeled direct-drive electric vehicle is driven by induction in-wheel motor, which can precisely control the in-wheel motor with the same and differential speed and take place of the mechanical differential and transmission device of traditional vehicles. High dynamic traction is realized, which is based on virtual master-slave control strategy of Ackerman steering model and direct torque control of in-wheel motor. The system has been simulated in the Matlab/Simulink via its stability analysis. The result shows that when the load torque is different between two in-wheel motors, the steady tracking accuracy is good, and its dynamic integral error is small.